Black nerd problems - Evans, William, III (William H.); Holmon, Omar (Gallery Books, 2021)
"The creators of the popular website Black Nerd Problems bring their witty and unflinching insight to this engaging collection of pop culture essays on everything from Mario Kart and The Wire to issues of representation and police brutality across media"--